Traversing the urban as a woman in Cairo and Aswan - Mourad, Mennat-Allah Yehia (AUC Knowledge Fountain, 2015)
This thesis explores the hierarchical dynamics that govern the everydayness of women’s relationship to spaces. I argue that our conceptual understanding of space, especially through terms such as modern, cosmopolitan, tribal, village...etc, are all part of a lexicon that makes our everyday, but that also how we traverse the city, and the choices that we make of where to go and how to get there is an integral contributor of how a city is not only imagined but lived, and thus how the social imaginations that we believe govern our everyday is actually re-iterated. I argue that our choices as influenced by neoliberal capital has been influencing in turn our everyday and how it is not separate from the overarching events of rupture that occurred in 2011 through to 2013, and how these ruptures helped make the invisible of the hierarchical dimensions of the city visible.